Pollen Morphology of the Tribe Vernonieae (Compositae) in Thailand - BUNWONG, SUKHONTHIP; CHANTARANOTHAI, PRANOM (Tropical Natural History, 2008)
The pollen morphology of 27 species from five genera in the tribe Vernonieae (Compositae) was examined with light and scanning electron microscopy. Three major pollen types, based on exine sculpturing, could be recognized; subechinolophate, echinolophate and psilolophate. The pollen is spheroidal and isopolar. Most (21/27) of the species’ pollen are echinolophate except for four and two species which are subechinolophate and psilolophate, respectively. The pollen, based on aperture type, can be divided into tricolporate, triporate and six-porate. The distribution of triporate and tricolporate pollen between species does not support Robinson’s (1999a) notion of restriction to the genera Elephantopus and Vernonia, respectively, but rather tricolporate and porate grains are found in woody plants and herbs, respectively. The six-porate pollen reported here in the Vernonia tribe has not been recorded within the Compositae family before and extends the diversity of pollen morphology and evolution.